3′‐Desmethylarctigenin induces G2/M cell cycle arrest and apoptosis through reactive oxygen species generation in hepatocarcinoma cells. (30th August 2019) - Zhang, Enxiang; Wang, Xiuling; Liu, Xiaoyi; Liang, Min; Hu, Hongbo; Yin, Shutao
Abstract : Previous studies have shown that arctigenin is a promising chemopreventive or therapeutic agent against various cancers. However, less is known about anticancer activity of 3′‐desmethylarctigenin (3′‐DMAG), which is a biotransformed product from arctigenin or arctin. In this study, we compared the anticancer activity of 3′‐DMAG with its parent compound arctigenin and demonstrated that 3′‐DMAG exerted a more potent inhibitory effect on HepG2 cells than arctigenin. Mechanistically, reactive oxygen species generation played an apical role in 3′‐DMAG‐induced G2/M cell cycle arrest and apoptosis in HepG2 cells. Furthermore, the Chk2–Cdc25c–Cdc2–cyclin B1 cascade was found to contribute to the cell cycle arrest, whereas the activation of mitochondrial pathway was involved in the cell apoptosis by 3′‐DMAG. Additionally, a mouse xenograft hepatocellular carcinoma model was used to evaluate the antitumor effect of 3′‐DMAG in vivo, and the results indicated that 3′‐DMAG treatment significantly inhibited tumor growth without apparent toxicity. Taken together, 3′‐DMAG is highly effective against liver cancer both in vitro and in vivo. The findings of the present study suggest that this compound deserves to be further investigated for its potential anticancer activity.